Analysis of electromagnetic characteristics of the main transformer caused by pantograph-catenary disconnection in high speed train. (1st January 2014) - Wang, Jin; Yang, Zhongping; Lin, Fei; Cao, Junci; Liu, Wenzheng
With the increasing speed of the high-speed train, the disconnection of pantograph-catenary system becomes more frequent which will lead to DC magnetic bias of the main transformer. A coupled finite element model of pantograph-catenary system and a 3D coupled field-circuit model of the main transformer have been set up to analyse this issue. This paper has analysed the current harmonic, electromagnetic field characteristics and leakage inductance which all cause by DC magnetic bias. Results show that with the rising of DC magnetic bias, the current harmonic and secondary leakage inductance are increasing and the primary leakage inductance is decreasing. Variation rules of electromagnetic field have been summed up in this paper.